White matter pathways as both a target and mediator of health behaviors. Issue 1 (11th May 2018) - Porter, Alexis; Leckie, Regina; Verstynen, Timothy
Abstract: Health behaviors arise from the dynamics of highly interconnected networks in the brain and variability in these networks drives individual differences in behavior. In this review, we show how many factors that predict the physical health of the body also correlate with variability of the myelinated fascicles, called white matter, that connect brain regions together. The general pattern present in the literature is that as predictors of physical health decline, there is often a coincident reduction in the integrity of major white matter pathways. We also highlight a plausible mechanism, inflammatory pathways, whereby health‐related activation of the immune system can impact the myelin sheath, a protective tissue that facilitates long range communication in the brain. The growing body of evidence supports the hypothesis that degrading health in the periphery may disrupt the communication efficiency of the macroscopic neural circuits that mediate complex behaviors, which can in turn contribute to poorer physical health. Abstract : In this review, we show how many factors that predict the physical health of the body also correlate with variability of the myelinated fascicles, called white matter, that connect brain regions together. We also highlight a plausible mechanism, inflammatory pathways, whereby behaviorally induced changes in the body could impact cellular pathways in the central nervous system.